The Role of Viral Marketing Value “Instagram” in Building Customer Relationships Performance: Perspectizing SDL Theory - Andi Setiawan; Astohar Astohar; Bagus Yunianto Wibowo; Rif’ah Dwi Astuti; Wahyuni, Sri (International Journal of Education, Vocational and Social Science, 2025)
In the context of social media platforms, it is important for MSMEs to differentiate themselves in order to attract the attention of potential customers. This study uses the Viral Marketing Value Effect Model to examine the role of social media platforms in customer relationship performance. Data from 219 culinary MSMEs in Central Java shows that social media influencers and characteristics have an effect on customer relationship performance, while social media influencers do not. The study also explores how viral marketing value moderates the relationship between social media influencers and social media characteristics on customer relationships. The findings provide insights that extend the Service Dominant Logic (SDL) theory to social media marketing literacy in MSMEs.